(untitled) (International Journal of Occupational Safety and Health, 2026)
Introduction: India’s construction industry constitutes 16.4% of worldwide occupational dangers, although employing just 7.5% of the labor force, indicating significant safety shortcomings. Contributing elements encompass ineffective communication, absence of protective equipment, hazardous work practices, insufficient training, psychological strain, deficient safety culture, and restricted legal adherence. Notwithstanding the sector’s multidisciplinary characteristics necessitating robust safety planning, insufficient protections persistently result in significant accidents and productivity declines. Methods: This study investigates methods to improve safety performance utilizing Building Information Modeling (BIM) for proactive risk detection and real-time monitoring, alongside Blockchain for transparent and tamper-proof compliance administration. Results: Blockchain guarantees secure compliance records, while BIM facilitates early hazard detection, improved risk visualization, and coordination. Together, these features improve accountability, lower accident rates, and increase overall construction safety. Conclusion: By enabling proactive risk management and transparent compliance, lowering accidents, increasing productivity, and directing stakeholders toward successful digital adoption, the integration of BIM and Blockchain enhances construction safety.